Adsorption of β-Picoline on the Adsorbents Produced from Spent Bleaching Earth - MAHRAMANLIOGLU, MEHMET (Asian Journal of Chemistry, 2010)
The sorption of β-picoline by acid treated spent bleaching earth was studied to examine the potentiality of this material in treatment systems. The effect of time, pH, initial concentration on the adsorption of β-picoline was studied. Lagergren first order rate equation was used to describe the adsorption rate of β-picoline and adsorption rate constants were calculated. Rate constants of intraparticle diffusion were calculated. Adsorption isotherms were modelled by the Langmuir equation and the isotherm constants of this isotherm were calculated. The dependence of the adsorption of β-picoline on the pH of the solution was studied to achieve the optimum pH value and a better understanding of the adsorption mechanism. The maximum adsorption was found to occur at pH 7.85. Giles isotherm was used and adsorption type was determined.